Pengaruh Persepsi Strategi Paid Promote di Media Sosial Instagram sebagai Alat Pemasaran terhadap Perilaku Pembelian Online Perspektif Ekonomi Islam - Luluk Illiyah; Irdlon Sahil (Journal of Economic and Islamic Research, 2022)
Perception of marketing strategy through paid promote advertising services is an effective effort or strategic and creative steps in overcoming the problems of every company or online business owner. The purpose of this study was to determine whether there is an effect of paid promote strategy, to find out how the effect of paid promote as a marketing tool affects online purchasing behavior and to determine the Islamic economic perspective regarding paid promote strategy. Due to the rapid development of technology, online business owners must be able to compete with competitors. One of them is in terms of marketing, because marketing is the spearhead of a company. So that an existing product can be recognized by the wider community. The design of this research is quantitative research. With the population of this study as many as 75 respondents. The sampling technique uses saturated samples. Data collection techniques using a questionnaire as many as 20 statement items using a Likert scale. Data analysis techniques to answer the hypothesis using simple linear regression analysis. Based on the results of the study, it shows that there is a positive and significant influence on the perception of paid promote strategy as a marketing tool on online buying behavior. This is evidenced by the coefficient of determination R square of 64.7%. This means that there is a significant influence between the perception variable paid promote strategy (X) on the online purchasing behavior variable (Y). One of the influencing indicators is attractive advertisements that can lead to online buying behavior. This paid promote strategy is in accordance with the perspective of Islamic economics because in terms of its activities it uses principles that are in accordance with Islamic law by doing marketing that does not contain gharar element